A intervenção do professor de educação física no processo de exteriorização da sexualidade das crianças a partir das manifestações corporais, à luz dos pensamentos de Bourdieu - Manzini, Beatriz Rodrigues Kavahara [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This research aims to analyze the attitudes of physical education teachers in the diverse manifestations of their students' sexuality. Thinking that the social construction of the body takes place from the experiences lived along the life trajectory of the agent, we identify the interferences acquired as structuring devices of behavior and as product of them, the attitudes of these teachers. When we speak of sexuality we refer to the object of an identity built from a historical process and social influences of institutions such as school, family, church and society. Being a programmatic content within the National Curriculum Parameters (NCPs), the Transversal Themes debate sexuality as a social issue, which must be addressed by the educators in their disciplines. Of sociological character, This research had the qualitative research as a methodological contribution with semi-structured interviews. Three physical educators were interviewed, who taught in the first years of elementary school I, in public institutions, in a municipality in the interior of São Paulo. The script used to guide the interviews was composed of 52 questions capable of identifying the social trajectory of these agents. Analyzes were performed using Bourdieu's analysis categories. As found results, we can rectify the theory based on observing social characteristics marked in the behavior of educators, in their interventions. Therefore, we elucidate the formation of the educators' habitus as determinant social structures, acquired from the inside and restructured by the environment in which the agent is inserted.

Esta pesquisa tem como objetivo analisar as atitudes dos professores de Educação Física nas diversas manifestações da sexualidade de seus alunos. Uma vez que, a construção social do corpo dá-se a partir das experiências vivenciadas ao longo da trajetória de vida do agente, identificamos como dispositivos estruturantes do comportamento, as interferências adquiridas e como produto delas, as atitudes destes professores. Quando falamos de sexualidade, nos referimos ao objeto de uma identidade construída a partir de um processo histórico e de influências sociais de instituições como escola, família, igreja e sociedade. Sendo conteúdo programático dentro dos PCN´s (Parâmetros Curriculares Nacionais), os Temas Transversais debatem a sexualidade como questão social, os quais devem ser abordados pelos educadores em suas disciplinas. De caráter sociológico, esta investigação teve como aporte metodológico a pesquisa qualitativa com entrevistas semi- estruturadas , como ferramenta. Foram entrevistados três educadores físicos, que lecionavam nos primeiros anos do ensino fundamental I, em instituições públicas, em um município do interior paulista. O roteiro utilizado para nortear as entrevistas foi composto por 52 questões capazes de identificar a trajetória social desses agentes. As análises foram realizadas por meio das categorias de análise de Bourdieu. Como resultados encontrados, pudemos ratificar a teoria embasada, ao observar características sociais marcadas no comportamento dos educadores, em suas intervenções. Elucidamos, portanto a formação do habitus dos educadores como estruturas sociais determinantes, adquiridas à priore no seio familiar e reestruturadas pelo meio em que o agente está inserido.
The professor of Physical Education in the process of exteriorization of the sexuality of children from corporate manifestations, in the light of the thoughts of Bourdieu
Keywords: Educação Física; Sexualidade; Habitus; Physical Education; Sexuality